Ultrasound manifestations of enchondroma protuberans: Two case reports. Issue 25 (June 2018) - Xiang, Xi; Cheng, Shan; Yang, Yu-jia; Qiu, Li
Abstract: Rationale: We report two rare cases of enchondroma protuberans originating from phalanxes. Patient concerns: The patients visited doctors for a palpable mass in their phalanx without any pain or discomfort. Diagnoses: Biopsy is the gold standard for the diagnosis of enchondroma protuberans. Radiographs usually provide important imaging information, while studied on the ultrasound manifestation of enchondroma protuberans are still limited. In our cases, significant information about ultrasound manifestation of enchondroma protuberans were presented. Sonographic examination of enchondroma protuberans revealed a hypoechoic mass located in and beyond the medullary cavity of bone through the interrupted bone cortex, and blood flow signals were usually not abundant. Interventions: Patients were subsequently referred for surgical removal and the masses were confirmed by following pathological examination. Outcomes: After surgery, the patients recovered well with no relapse within 2 years. Lessons: Enchondroma protuberans is a rare form of benign enchondroma. Enchondroma protuberans can present as an intramedullary hypoechoic mass extending to the surrounding soft tissue via the discontinuous cortex line on ultrasound. Ultrasound can provide important information for the diagnosis of enchondroma protuberans.